KUALITAS HIDUP LANSIA DIABETES MELLITUS DIHUBUNGKAN DENGAN TINGKAT KECEMASAN DAN DUKUNGAN SOSIAL PADA NEW ERA PANDEMI COVID-19 - Siregar, Rinco; Gultom, Rumondang; Simanjuntak, Siska Evi; Anwairi, Ubay (Jurnal Ilmiah Keperawatan IMELDA, 2023)
During the Coronavirus disease-19 (COVID-19) pandemic, especially in the elderly with Diabetes Mellitus (DM), they often experience anxiety which affects their quality of life, in addition, DM disease itself also affects the quality of life of the elderly. This study aim was to determine the relationship between the level of anxiety and family social support on the quality of life of elderly people with DM in the new normal era of COVID-19 pandemic in Langkat Regency.This study was descriptive correlation with cross-sectional design. The sample in this study was selected using this purposive sampling technique for as many as 140 elderly people who had DM and lived together with their families. The Zung Self-Rating Anxiety Scale (ZSRAS/ZSAS) measures the anxiety of the elderly, the Multidimensional Scale of Perceived Social Support (MSPSS) measures the social support obtained by the elderly, and the Older People's Quality of Life Brief Questionnaire (OPQoL-Brief) measures the quality of life of the elderly. The result showed that there was a negative relationship between the level of anxiety and the quality of life of elderly people with DM (P=000; <0.05; r: -0.331), there was a positive relationship between social support and the quality of life of elderly people with DM (P=0.001; <0.05; r: 0.647). It can be concluded that elderly with DM who experience moderate anxiety, and who receive high social support, have a good quality of life. It is recommended that health workers provide interventions to reduce anxiety levels and improve social support for the elderly.